Winter, spring, summer or fall: temporal patterns in placenta-mediated pregnancy complications—an exploratory analysis - Jeppegaard, Maria; Rasmussen, Steen C.; Anhøj, Jacob; Krebs, Lone (Archives of gynecology and obstetrics, 2024)
Purpose Placenta-mediated pregnancy complications, like growth restriction and hypertensive disorders, are leading causes of maternal, fetal and neonatal morbidity and mortality in high-income countries. The purpose was to investigate if there is a seasonal variation in placenta-mediated pregnancy complications (small for gestational age, intrauterine growth restriction, preeclampsia, preterm birth and intrauterine fetal death). Methods This is a Danish cohort study including all singleton deliveries at gestational week 22 up to and including week 41 conceived from December 2006 to November 2016 ( N = 555,459). We used statistical process control charts to visualize data and to test for patterns of non-random variation in data over time for pregnancies with risk factors (BMI, diabetes, in vitro fertilization, maternal age > 40 years, primipara, previous caesarean and smoking) and each of the following outcome: fetal growth restriction, hypertensive disorders, preterm birth and intrauterine fetal death. The study was approved by the Danish Data Protection agency; REG-039-2019. Results We found a seasonal pattern in hypertensive disorders during pregnancy with dips in pregnancies conceived in the fall season and highest risk by conception in the spring and summer season. We found no apparent seasonality in cases of preterm delivery, small for gestational age and intrauterine mortality. Individual risk factors (e.g. smoking and obesity) for placenta-mediated complicated over time were in consistency with the general trends. Conclusions We found a significant seasonal variation in the risk of hypertensive disorders of pregnancy with highest risk by conception in the spring and summer season. This study found no seasonal variation in other placenta-mediated complications.